Tuning spectral properties of phenothiazine based donor-pi-acceptor dyes for efficient dye-sensitized solar cells - Marszalek, Magdalena; Nagane, Satyawan; Ichake, Amol; Humphry-Baker, Robin; Paul, Vincent; Zakeeruddin, Shaik M.; Graetzel, Michael (Journal of Materials Chemistry, 2012)
Two novel metal-free organic donor-pi-acceptor dyes were synthesized using electron-rich 10-butyl-(2-methylthio)-10H-phenothiazine as a donor and cyanoacrylic acid as an acceptor. The spectral response of the dye was tuned by introducing a vinylene thiophene pi-bridge. Obtained optical and electrochemical properties of the dyes seemed to be promising in terms of employing them as light harvesters in dye-sensitized solar cells (DSCs). The efficiencies of the devices under standard AM 1.5G (100 mW cm(-2)) conditions reached 7.3% with volatile electrolyte. The differences in the photovoltaic parameters of these DSCs were explained by comparing the results of electrochemical impedance spectroscopy (EIS) measurements and transient photovoltage and photocurrent decay experiments.

Fluorescent sophorolipid molecular assembly and its magnetic nanoparticle loading: a pulsed laser process - Singh, Pradeep Kumar; Mukherji, Ruchira; Joshi-Navare, Kasturi; Banerjee, Abhik; Gokhale, Rohan; Nagane, Satyawan; Prabhune, Asmita; Ogale, Satishchandra (Green Chemistry, 2013)
We report realization of strong green fluorescence in a fully biocompatible highly spherical mesoscale molecular assembly of sophorolipid created by pulsed UV laser processing of a water-based dispersion of sophorolipid. Remarkably, the said fluorescence is totally absent in the original molecule of sophorolipid and is thus the property of the pulsed laser induced modifications in the molecule and the assembly. We have separately examined the consequences of laser irradiation for glucose and oleic acid components which form the sophorolipid. This fluorescence character appears to be driven by the oleic acid component while the assembly process is assisted by the glucose component. Importantly the laser synthesized mesostructures can be easily redispersed in an aqueous medium after being dried and can also be loaded with magnetic nanoparticles (magnetite) for inducing the hyperthermia effect.

Structural variations of D-pi-A dyes influence on the photovoltaic performance of dye-sensitized solar cells - Marszalek, Magdalena; Nagane, Satyawan; Ichake, Amol; Humphry-Baker, Robin; Paul, Vincent; Zakeeruddin, Shaik M.; Gratzel, Michael (RSC Advances, 2013)
Two new organic D-pi-A dyes containing identical pi-conjugated spacer and anchoring/acceptor moieties but different donor groups were designed and synthesized. These dyes containing didodecylcyclopentadithiophene (CPDT) as a spacer, cyanoacrylic acid as an acceptor and N-butyl-carbazole or N-butyl-phenothiazine moieties as electron donor groups are labelled as V4 and V11 dyes, respectively. The variation in the donor group of these two dyes, that influences the photophysical, electrochemical and photovoltaic parameters, was investigated. The highest photovoltaic conversion efficiency of 7.5% was obtained with V4 dye at AM 1.5 G full sunlight intensity (100 mWcm(-2)). Comparison of phenothiazine donor dyes with two different pi-conjugated spacers, CPDT (V11) and vinyl thiophene (V7) containing devices shows that the V-oc of V7 dye is lower than that of V11 due to the downward shift of the conduction band edge. Transient photovoltage and electrochemical impedance spectroscopy measurements were performed to explain the differences in the PV parameters by varying the donors and/or spacer groups.

CH3NH3PbI(3-x)(BF4)(x): molecular ion substituted hybrid perovskite - Nagane, Satyawan; Bansode, Umesh P.; Game, Onkar S.; Chhatre, Shraddha; Ogale, Satishchandra (Chemical Communications, 2014)
A molecular ion (BF4-) substituted hybrid perovskite CH3NH3PbI(3-x)(BF4)(x) is synthesized. The substituted perovskite shows significant enhancement in electrical conductivity at low frequencies and improved photoresponse under AM1.5 illumination as compared to the perovskite (CH3NH3PbI3).

Indanthrone derived disordered graphitic carbon as promising insertion anode for sodium ion battery with long cycle life - Suryawanshi, Anil; Mhamane, Dattakumar; Nagane, Satyawan; Patil, Shankar; Aravindan, Vanchiappan; Ogale, Satishchandra; Srinivasan, Madhavi (Electrochimica Acta, 2014)
We report facile, one step synthesis of disordered graphitic carbon by high temperature (1000 degrees C) pyrolysis of indanthrone dye (ID). The pyrolysed carbon is disordered in nature and the same is clearly evidenced by various analytical techniques like X-ray diffraction, Raman spectroscopy and high resolution transmission electron microscopy. Na-insertion properties of such indanthrone dye derived disordered graphitic carbon (IDDGC) is evaluated in half-cell assembly (Na/IDDGC). The test cell delivered a reversible capacity of similar to 160 mAh g(-1) at current density of 25 mAg 1. In addition, excellent cycling profiles are noted for such IDDGC, which retains 67% of initial reversible capacity after 500 cycles. The present study clearly highlights the importance of disorder in the graphitic carbon for efficient Na-ion storage. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: anode; disordered carbon; indanthrone; Na-ion battery

CH3NH3Pb(BF4)(3) and (C4H9NH3)2Pb(BF4)(4) family of 3D and 2D perovskites without and with iodide and bromide ions substitution - Nagane, Satyawan; Ogale, Satishchandra B. (Journal of Physical Chemistry Letters, 2016)
We report the synthesis of fully molecular ion (BF4 )-based organicinorganic hybrid perovskite CH3NH3Pb(BF4)(3), which is a wide band gap semiconductor, and the same can be easily tuned toward the visible by the incorporation of bromide or iodide ions in the crystal framework simply by changing lead precursors. We have also successfully transformed the distorted 3D molecular-ion-induced perovskite to 2D (C4H9NH3)(2)Pb(BF4)(4), (C4H9NH3)(2)PbBr(4x)(BF4)(x), and (C4H9NH3)(2)PbI(4x)(BF4)(x) perovskites that exhibit the optical absorption over the UV to visible region. The thin films of molecular-ion-containing 2D perovskites with Br and I anions show blue and green luminescence, respectively, under UV illumination.

Hybrid perovskite quantum nanostructures synthesized by electrospray antisolvent-solvent extraction and intercalation - Naphade, Rounak; Nagane, Satyawan; Shanker, G. Shiva; Fernandes, Rohan; Kothari, Dushyant; Zhou, Yuanyuan; Padture, Nitin P.; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2016)
Perovskites based on organometal lead halides have attracted great deal of scientific attention recently in the context of solar cells and optoelectronic devices due to their unique and tunable electronic and optical properties. Herein, we show that the use of electrospray technique in conjunction with the antisolventsolvent extraction leads to novel low-dimensional quantum structures (especially 2-D nanosheets) of CH3NH3PbI3- and CH3NH3PbBr3-based layered perovskites with unusual luminescence properties. We also show that the optical bandgaps and emission characteristics of these colloidal nanomaterials can be tuned over a broad range of visible spectral region by compositional tailoring of mixed-halide (I- and Br-based) perovskites.
Keywords: 2D nanostructure systems; antisolvent-solvent extraction; bandgap tuning; electrospray; nanosheets; perovskite; quantum dots

Low-dimensional hybrid perovskites as high performance anodes for alkali-ion batteries - Tathavadekar, Mukta; Krishnamurthy, Shrreya; Banerjee, Aparna; Nagane, Satyawan; Gawli, Yogesh; Suryawanshi, Anil; Bhat, Suresh; Puthusseri, Dhanya; Mohite, Aditya D.; Ogale, Satishchandra (Journal of Materials Chemistry A, 2017)
State-of-the-art Li (or Na) ion batteries work by insertion/extraction of the alkali metal ions into a porous electrode material, where the overall capacity is strongly dependent on the accessibility of the host material interior to the ions. On the other hand, the performance stability depends on various factors governed by the specific constitution of the electrode. Here we show that molecularly engineered low-dimensional hybrid perovskites can work as excellent anode materials for alkali-ion batteries. We measure a high reversible capacity of 646 mA h g(-1) at 100 mA g(-1) with good stability tested up to 250 cycles for the benzidine mediated lead iodide based 1D system. An ex situ analysis of the electrodes reveals that the storage primarily occurs via the Li-x(or Na-x)Pb alloying/de-alloying process. We anticipate that these results open a new direction for the use of low-dimensional hybrid perovskites for energy storage applications.
Keywords: Generation; Inorganic-Organic Hybrid; Lead Iodide; lithiation-intramolecular electrophilic reaction; Na-Air Battery; Negative Electrodes; Organometal Halide perovskites; PB; Sequential Deposition; Solar-cells

Phenothiazine-based D-A-π-A dyes for highly efficient dye sensitized solar cells: effect of internal acceptor and non-conjugated π-spacer on device performance - Nagane, Satyawan; Ichake, Amol; Agrawal, Ishita; Sadhanala, Aditya; Friend, Richard H.; Ogale, Satishchandra; Wadgaonkar, Prakash P. (ChemPlusChem, 2017)
Three new D-A-pi-A metal-free organic dyes based on phenothiazine as a donor (D) and non-conjugated pi-spacer were designed and synthesized. The incorporation of different 'internal acceptors' (electron traps) such as benzothiadiazole (BTD), benzotriazole (BTA), and pyridine were shown to allow systematic tuning of the energy levels and the photophysical properties. The AI-1 dye showed lower electronic disorder compared with the other two dyes. The efficiencies achieved with AI-1, AI-2, and AI-3 dyes were 8.5% (J(sc) = 15.42 mA cm(-2), V-oc = 0.78 V, FF = 68%), 7% (J(sc) = 12.8 mA cm(-2), V-oc = 0.78 V, FF = 68%) and 6.7% (J(sc) = 11.57 mA cm(-2), V-oc = 0.82 V, FF = 68.26 %), respectively. The incorporation of non-conjugated phenothiazine as a p-spacer in D-A-pi-A dyes showed remarkable enhancement in the photovoltaic performance of dye-sensitized solar cell (DSSC) devices. The sealed DSSC devices with iodide/tri-iodide (I-/I-3(-) @)based liquid electrolyte showed promising stability under ambient conditions.

Synthetic manipulation of hybrid perovskite systems in search of new and enhanced functionalities - Naphade, Rounak; Nagane, Satyawan; Bansode, Umesh; Tathavadekar, Mukta; Sadhanala, Aditya; Ogale, Satishchandra (ChemSusChem, 2017)
Over the past few years the organic-inorganic hybrid perovskite systems have emerged as a promising class of materials for photovoltaic and electroluminescent thin-film device applications, in view of their unique set of tunable optoelectronic properties. Importantly, these materials can be easily solution-processed at low temperatures and as such are amenable to facile molecular engineering. Thus, a variety of low-dimensional forms and quantum structures of these materials can be obtained through strategic synthetic manipulations through small molecule incorporation or molecular ion doping. In this Minireview, we specifically focus on these approaches and outline the possibilities of utilizing these for enhanced functionalities and newer application domains.